LINGGA BERHIAS PADMA ASTADALA - Nyoman Rema; Nyoman Sunarya (Balai Arkeologi Bali, 2015)
Worship of Lord Siwa with medium lingga is very popular in Bali, evidenced by the large number of lingga on holy places in Bali, with various forms. The purpose of this study was to determine the form, function, and meaning of the lingga in the region. Results of this study are different forms of the lingga, which is spread over the area in Penebel District. However, as object of research is decorated with padma aadala lingga at Jambe Langu and Puseh Sunantaya Temple. The lingga is the lingga pseudo lingga consisting of Siwabhaga, rectangular pedestal decorated with padma aadala. Lingga is used as a medium of worship of Lord Siwa to invoke safety. Lingga is meaningful as a symbol of inner purity, creation and freedom.Pemujaan Dewa Siwa dengan media lingga sangat populer di Bali, dibuktikan dengan bayaknya jumlah lingga pada tempat-tempat suci di Bali, dengan berbagai bentuk. Tujuan penelitian ini adalah untuk mengetahui bentuk, fungsi, dan makna lingga di kawasan tersebut. Hasil penelitian ini berupa berbagai bentuk lingga, yang tersebar di kawasan Kecamatan Penebel. Namun, yang dijadikan objek penelitian adalah lingga yang berhiaskan padma aadala di Pura Jambe Langudan Pura Puseh Sunantaya. Lingga tersebut adalah lingga semu yang terdiri atas Siwabhaga, lapik segi empat yang berhiaskan padma aadala. Lingga ini digunakan sebagai media pemujaan kepada Dewa Siwa untuk memohon keselamatan. Lingga ini bermakna sebagai simbol kesucian batin, penciptaan dan kebebasan.